Shift work and long-term injury among police officers - John M Violanti; Desta Fekedulegn; Michael E Andrew; Luenda E Charles; Tara A Hartley; Bryan Vila; Cecil M Burchfiel (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: Our previous work has suggested that the incidence of any occurrence of injury leave among police officers is higher on night shifts. In this study, we extended our inquiry to determine whether the incidence of long-term injury leave varies across shifts. METHODS: Police officers (N=419) from an urban department were included in the analysis. Daily payroll work history data from 1994-2010 was collected. Injury leave duration was examined ranging from ≥1-≥90 days. Poisson regression models were used to compute incidence rates (IR) and incidence rate ratios (IRR) of long-term injury. RESULTS: Cumulative incidence of injury for different durations of leave defined as ≥1, ≥5, ≥10, ≥15, ≥30, and ≥90 days were 61.3%, 45.4%, 39.9%, 33.9%, 26.5%, and 9.6% respectively. Age-and gender adjusted IRR of long-term injury (≥90 days) for night versus day shifts was IRR 3.12, 95% confidence interval (95% CI) 1.35-7.21 and IRR 2.21, 95% CI 1.04-4.68, for night versus afternoon shifts. Among all durations examined, the largest IRR was for injury ≥90 days, night versus day shifts (IRR 3.12, 95% CI 1.35-7.21). CONCLUSIONS: Night shift work was significantly associated with long-term injury among police officers after adjustment for age and gender. Although type of injury was not available, it is possible that variation in injury type across shifts might account for some of this association.